Thermal decomposition study of perchlorate-based metal-free molecular perovskite DAP-4 mixed with ammonium perchlorate - Xiao-Jun Feng; Kun Zhang; Yu Shang; Wen Pan (Case Studies in Thermal Engineering, 2022)
The molecular perovskite energetic materials (H2dabco)[NH4(ClO4)3] (DAP-4, H2dabco2+ = 1,4-diazabicyclo[2.2.2]octane-1,4-diium), limits its separate application in explosives duo to the severe negative oxygen balance. Therefore, it is of great significance to study the thermal decomposition performance of DAP-4 in the presence of AP oxidant. In this work, the differential scanning calorimetry-thermogravimetry-mass spectrometry-fourier transform infrared spectroscopy (DSC-TG-MS-FTIR) coupling technique, thermal decomposition kinetics, and in-situ FTIR method were used to analyze the thermal decomposition characteristics, and the variation of condensed phase characteristic groups of DAP-4 and the DAP-4/AP mixtures. The results show that AP has negligible effect on thermal decomposition temperature of DAP-4 but can prolong the total decomposition time of DAP-4 by 5.55 min. In addition, thermal decomposition of AP and DAP-4 in the mixture is independent of each other, and the thermal decomposition mechanism of DAP-4/AP mixtures is more complicated than that of DAP-4 alone. Thermal decomposition of DAP-4/AP mixture firstly experiences decomposition of AP at low temperature, the inside crystal transformation of DAP-4, the H+ transfer, and then cage skeleton collapse-induced redox reaction to generate large amount of heat which can shift forward the high-temperature decomposition peak of AP.